THE COURSE OF PREGNANCY AND CHILDBIRTH IN WOMEN OF LATE REPRODUCTIVE AGE - Светлана Ивановна Елгина; Полина Андреевна Овчарова; Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (The Publishing House Medicine and Enlightenment, 2023)
According to Rosstat, the birth rate in the Russian Federation for 2022 decreased by 8.6 % compared to the same indicators for 2021. The average age of a woman at the birth of a child is 28 years 10 months. At the same time, the share of women of late reproductive age in the age structure of fertility is growing. However, with increasing age of a woman, the influence of factors that increase the risks of adverse obstetric and perinatal outcomes increases. Women of late reproductive age have an older age of the first birth, more often resort to the use of assisted reproductive technologies, are at risk for preeclampsia, premature birth and require an individual approach to the management of pregnancy and childbirth.